Interest Survey of Members of Student Activity Unit (UKM) Badminton Surabaya State University - Gilang Kurniaffan; Afif Rusdiawan; Pudjijuniarto; Indra Himawan Susanto (Jurnal Pendidikan Jasmani (JPJ), 2026)
Student Activity Unit (UKM) Badminton Surabaya State University is a means of developing the interests and talents of students in the field of sports. Member interest plays an important role in supporting the participation and success of SME activities. This study aims to determine the level of interest of badminton SME members of Surabaya State University. Research using quantitative descriptive methods with survey techniques. The subjects of the study were 117 active members of badminton SMEs for the period 2024/2025 male and female. The research instrument is a Likert scale questionnaire that includes intrinsic factors (attention, feelings of pleasure, and activity) and extrinsic factors (role of coach, facilities, family, and environment). The results showed that the interest of badminton SME members was in the medium category as many as 66 respondents (56.41%). High category of 14.53%, low category of 17.95%, very high category of 5.13%, and very low category of 5.98%. Intrinsic factor and extrinsic factor are both in the medium category. It can be concluded that the interest of badminton SME members of the State University of Surabaya is quite good but not optimal, so efforts are needed to increase internal motivation and external support to increase member participation.